Transit timing analysis of the exoplanet TrES-5 b. Possible existence of the exoplanet TrES-5 c. Issue 1 (19th June 2018) - Sokov, Eugene N; Sokova, Iraida A; Dyachenko, Vladimir V; Rastegaev, Denis A; Burdanov, Artem; Rusov, Sergey A; Benni, Paul; Shadick, Stan; Hentunen, Veli-Pekka; Salisbury, Mark; Esseiva, Nicolas; Garlitz, Joe; et al.
ABSTRACT: In this work, we present transit timing variations detected for the exoplanet TrES-5b. To obtain the necessary amount of photometric data for this exoplanet, we have organized an international campaign to search for exoplanets based on the transit-timing variation (TTV) method and as a result of this we collected 30 new light curves, 15 light curves from the Exoplanet Transit Database (ETD) and 8 light curves from the literature for the timing analysis of the exoplanet TrES-5b. We have detected timing variations with a semi-amplitude of A ≈ 0.0016 d and a period of P ≈ 99 d. We carried out the N -body modelling based on the three-body problem. The detected perturbation of TrES-5b may be caused by a second exoplanet in the TrES-5 system. We have calculated the possible mass and resonance of the object: M  ≈ 0.24MJup at a 1:2 Resonance.